2013
DOI: 10.1371/journal.pone.0053390
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endocannabinoids and Cannabinoid-1 Receptors in Cerebrocortical Blood Flow Regulation

Abstract: BackgroundEndocannabinoids are among the most intensively studied lipid mediators of cardiovascular functions. In the present study the effects of decreased and increased activity of the endocannabinoid system (achieved by cannabinoid-1 (CB1) receptor blockade and inhibition of cannabinoid reuptake, respectively) on the systemic and cerebral circulation were analyzed under steady-state physiological conditions and during hypoxia and hypercapnia (H/H).Methodology/Principal FindingsIn anesthetized spontaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 91 publications
0
21
0
Order By: Relevance
“…CB1 expression presented a negative correlation with brain edema. Since CB1 is located in the end-foot of astrocytes [ 52 ], which are the principal glial cells that control ion exchange [ 53 ] and modulate cerebral blood flow [ 54 ], a lower expression of CB1 could affect the ionic balance and may lead to altered brain edema formation and resolution. Moreover, previous studies [ 55 , 56 ] with endothelium derived from human brain capillaries and microvessels demonstrated that one of the endogenous agonists of CB1 receptor, 2-arachydonoil glycerol (2-AG), inhibits some of the effects of endothelin-1 (ET-1).…”
Section: Discussionmentioning
confidence: 99%
“…CB1 expression presented a negative correlation with brain edema. Since CB1 is located in the end-foot of astrocytes [ 52 ], which are the principal glial cells that control ion exchange [ 53 ] and modulate cerebral blood flow [ 54 ], a lower expression of CB1 could affect the ionic balance and may lead to altered brain edema formation and resolution. Moreover, previous studies [ 55 , 56 ] with endothelium derived from human brain capillaries and microvessels demonstrated that one of the endogenous agonists of CB1 receptor, 2-arachydonoil glycerol (2-AG), inhibits some of the effects of endothelin-1 (ET-1).…”
Section: Discussionmentioning
confidence: 99%
“…In isolated middle cerebral arteries of rats, the endogenous CB1 receptor-agonist 2-AG was shown to attenuate vasoconstriction by the thromboxane mimetic U-46619 (Hillard et al, 2007 ). More recently, Iring et al ( 2013 ) did not find any significant influence of CB1 receptor activity on the regulation of cerebrocortical circulation under resting conditions in normotensive rats when activating endogenous AEA. There was, however, an indication of CB1 receptor-independent systemic hypertension as a result to enhancement of endocannabinoids.…”
Section: Resultsmentioning
confidence: 93%
“…One may suppose, however, that the effects of exogenously applied phyto-or endocannabinoids may be quite different from those induced by a complex endogenous control system. To overcome these limitations, in a recent study, the effects of suppressed endocannabinoid activity on the regulation of the cerebrocortical blood flow was investigated (102). AM-251, which is both antagonist and inverse agonist of the CB1-receptors (87,178), failed to alter significantly either the systemic or the cerebral circulation.…”
Section: Cerebrovascular Actions Of Exogenous and Endogenous Cannabinmentioning
confidence: 99%
“…The regulatory role of endocannabinoids in the systemic and cerebral circulation and the consequences of activating this system were investigated in an alternative way in a recent study (102). AM-404, a putative cannabinoid re-uptake inhibitor, which reportedly increases the endogenous levels of anandamide in the brain (64) induced triphasic changes in both the systemic and the cerebral circulation.…”
Section: Cerebrovascular Actions Of Exogenous and Endogenous Cannabinmentioning
confidence: 99%